2020
DOI: 10.3390/coatings10111057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Polishing Techniques on the Surface Characteristics of the Ti-6Al-4V Alloy and on Bacterial Adhesion

Abstract: Ti-6Al-4V, although widely used in dental materials, causes peri-implant inflammation due to the long-term accumulation of bacteria around the implant, resulting in bone loss and eventual failure of the implant. This study aims to overcome the problem of dental implant infection by analyzing the influence of Ti-6Al-4V surface characteristics on the quantity of accumulated bacteria. Ti-6Al-4V specimens, each with different surface roughness are produced by mechanical, chemical, and electrolytic polishing. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…The AFM micrographs of specimen D showed more undulate than other specimen that polished by non-chemical polishing methods. The above results of references [ 29 , 30 ] also prove that when the Ti-6Al-4V is polished by chemical polishing, the material removal rate of α phase and β phase of Ti-6Al-4V are different in the process of chemical polishing, and the micro peaks and valleys are left on the surface of the workpiece.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The AFM micrographs of specimen D showed more undulate than other specimen that polished by non-chemical polishing methods. The above results of references [ 29 , 30 ] also prove that when the Ti-6Al-4V is polished by chemical polishing, the material removal rate of α phase and β phase of Ti-6Al-4V are different in the process of chemical polishing, and the micro peaks and valleys are left on the surface of the workpiece.…”
Section: Discussionsupporting
confidence: 55%
“…In reference [ 29 ], when Ti-6Al-4V was polished by chemistry enhanced shear thickening polishing with different pH values, well-distributed surface peaks and valleys at regular intervals with the same size (about 5 μm) and height (about 10 nm) could be observed on the workpiece surface. In reference [ 30 ], the SEM images of Ti-6Al-4V specimen D, which is polished by chemical polishing, showed the α phase base and β phase on the workpiece surface. The AFM micrographs of specimen D showed more undulate than other specimen that polished by non-chemical polishing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Using hydrogen peroxide in our research during chemical etching shows promising results for the application of Ti-13Nb-13Zr surfacemodified alloy in implantology. The produced O 2 and OH can alter the permeability of a surface, e.g., of the Staphylococcus aureus cell membrane [78], which may result in the surface antimicrobial properties desired in implants [79,80]. It is worth paying attention to this issue and developing it in terms of the antibacterial properties of Ti-13Nb-13Zr surfaces after various types of modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical properties of the treated metal surface can be manipulated to alter bacterial adhesion and biofilm formation. It was reported that electrolytic polishing of the Ti-6Al-4V titanium alloy (which is widely used in medicine) is favorable to obtain a surface roughness of 10.33 nm ± 1.14 [ 106 ]. After the electropolishing process, the water contact angle was 92°, and the surface strongly inhibited the adhesion of S. mutans .…”
Section: Control Strategies For the Formation Of Clinically Important...mentioning
confidence: 99%